The interaction between supportive and unsupportive manager behaviors on employee work attitudes. Issue 6 (5th September 2016) - Teoh, Kevin Rui-Han; Coyne, Iain; Devonish, Dwayne; Leather, Phil; Zarola, Antonio
Abstract : Purpose: The purpose of this paper is to use social exchange theory (SET) to examine a model where supportive and unsupportive manager behaviors (SMB and UMB) interact to predict employees' engagement, job satisfaction and turnover intention. Design/methodology/approach: A cross-sectional online survey collected data from 252 UK-based employees of a global data management company. Findings: Factor analysis confirmed manager behaviors to consist of two constructs: supportive and unsupportive behaviors. Structural equation modeling indicated SMB predicted job satisfaction and turnover intentions, but not engagement. Job satisfaction, but not engagement, mediated the SMB-turnover intention relationship. UMB only predicted job dissatisfaction. Neither job satisfaction nor engagement mediated the UMB-turnover intention relationship. UMB undermined the positive relationship between SMB and turnover intention. Practical implications: The behaviors assessed can be integrated into various stages of a manager's development process to serve as guidelines of good practice. Crucially, findings suggest managers can exhibit both supportive and unsupportive behaviors, and that consistency in behaviors is important. The study also provides evidence that supportive managers can help reduce turnover intention through job satisfaction. Originality/value: SET was used as a framework for SMB, UMB and engagement. To the authors' knowledge this is the first study to examine the interaction between SMB and UMB.